The inclusion of downy mildews in a multi-locus-dataset and its reanalysis reveals a high degree of paraphyly in Phytophthora - F. Runge; S. Telle; S. Ploch; E. Savory; B. Day; R. Sharma; M. Thines (IMA Fungus)
Pathogens belonging to the Oomycota, a group of heterokont, fungal-like organisms, are amongst the most notorious pathogens in agriculture. In particular, the obligate biotrophic downy mildews and the hemibiotrophic members of the genus Phytophthora are responsible for a huge variety of destructive diseases, including sudden oak death caused by P. ramorum, potato late blight caused by P. infestans, cucurbit downy mildew caused by Pseudoperonospora cubensis, and grape downy mildew caused by Plasmopara viticola. About 800 species of downy mildews and roughly 100 species of Phytophthora are currently accepted, and recent studies have revealed that these groups are closely related. However, the degree to which Phytophthora is paraphyletic and where exactly the downy mildews insert into this genus in relation to other clades could not be inferred with certainty to date. Here we present a molecular phylogeny encompassing all clades of Phytophthora as represented in a multi-locus dataset and two representatives of the monophyletic downy mildews from divergent genera. Our results demonstrate that Phytophthora is at least six times paraphyletic with respect to the downy mildews. The downy mildew representatives are consistently nested within clade 4 (contains Phytophthora palmivora), which is placed sister to clade 1 (contains Phytophthora infestans). This finding would either necessitate placing all downy mildews and Phytopthora species in a single genus, either under the oldest generic name Peronospora or by conservation the later name Phytophthora, or the description of at least six new genera within Phytophthora. The complications of both options are discussed, and it is concluded that the latter is preferable, as it warrants fewer name changes and is more practical.